Analisis Pengendalian Persediaan Obat dengan Metode ABC dan VEN di Instalasi Farmasi RSUD Karangasem - Andika, Ni Kadek Wahyuning Kristina Dewi; Dewi, Dewa Ayu Putu Satrya; Farmani, Putu Ika (Bali International University, 2022)
Background: The quality of hospital health services is influenced by the availability of drugs. Drug inventory control at Pharmacy installation Karangasem Hospital only using a buffer stock method without calculations cause stock out drugs. Drugs inventory control using ABC-VEN, EOQ, SS and ROP analysis methods can unsure availability of drugs. Objective: This study aims to determine result of drug classification and control at Pharmacy instalation Karangasem Hospital. This study use a quantitative descriptive approach with a cross sectional research design and retrospective data collection for the period January-December 2021 at the Pharmacy Installation of Karangasem Hospital. Variables of this study are inventory control methods ABC-VEN, EOQ, SS and ROP. Data analysis using excel with data presentation using narration, tables, and diagrams. Result: The result of ABC analysis based on investment value, Category A 70%, Category B 20%, and Category C 10%. The result of VEN analysis, Category V 5%, Category E 90%, and Category N 90%. Top 10 drugs of category AE have a total investment value of IDR 8,889,652,150. The results of analysis top 10 drugs of AE category using the EOQ method can save procurement costs of Rp. 437.391.367, while the SS and ROP methods are effective for the use of fluctuating drugs. Conclusion:Based on the results of the analysis, ABC-VEN method can be used to determine which drug items should be prioritized based on the investment value and drug function, while the EOQ, SS and ROP methods are used to prevent stagnant dan stock out drugs.